The 5th Mexican Workshop on Fractional Calculus - Cruz-Duarte, Jorge (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint presents some of the selected works presented during the 5th Mexican Workshop on Fractional Calculus on October 5-7, 2022, hosted by the Tecnológico de Monterrey in Nuevo León. The works correspond to those recent proposals and applications on fractional calculus carried out in Mexico or by Latin American researchers related in one way or another to this country. Unfortunately, some of the papers we discussed during these three days of complete (not fractional) immersion in the non-integer operators were disregarded from this reprint, not because of their quality or relevance but due to reasons out of the academic domain. It is also worth mentioning that students of all levels, practitioners, and researchers attending this workshop participated in great critical discussions in every single session, including tutorials, plenary talks, accepted talks, and—not the least relevant to science—coffee breaks.